THE MODERATING EFFECT OF PERSONAL INNOVATIVENESS ON CURIOSITY AND PERCEIVED VALUE IN THE USE OF AUGMENTED REALITY TO ENHANCE LEARNING PROCESS: AN EXTENDED TECHNOLOGY ACCEPTANCE MODEL (E-TAM) PERSPECTIVE - Kende, Noel Carnitos Padang; Inan, Dedi I.; Yusuf, Irfan; Indra, Muhamad (STKIP PGRI Tulungagung, 2025)
Although various studies have attempted to investigate the use of Augmented Reality (AR) to enhance learning processes, very few are conducted to understand whether it can also ignite the cognitive func-tion. Therefore, study aims to examine personal innovativeness factor as a moderating effect on the relation between the AR and the curiosity and perceived value as the foundation to enhance learning processes by students. This research employes a quantitative method harnessing the Extended Technology Acceptance Model (E-TAM), with adding major and gender as control variables. Data were gathered using purposive sampling with 183 respondents, and analyzed using the PLS-SEM method. The results indicate that albeit personal innovativeness has no significant moderating effect to the relationships, the perceived ease of use, perceived usefulness, perceived of usability and flow experience of AR significantly influence the immersion AR (R2=71.1%), which subse-quently impacts curiosity (R2=40.9%) and perceived value (R2=54.9%), Further analysis also revealed differences in curiosity and perceived value based on gender and major. These findings provide new insights into the factors that influence the effectiveness of AR implementation in education.